Glass as a structural material - White, Rachel Lynn (Kansas State University, 2007)
Glass can be beautiful and strong, so why is it not used more often as a structural material? Most often the reasoning is because people fear its perceived fragile and dangerous nature. Although this is the perception, it is far from the reality. Structurally designed glass can even withstand higher loads than steel. The following report will present several advantages of using glass as a structural material. Because understanding the history of glass can foster a greater understanding of where the future of glass is headed, it is discussed early on. After this, the focus is on how to make a mixture of molten liquid into a structural member. The manufacturing process is at the root of the strength of glass, as are the material properties. The composition and properties of glass are addressed before discussing various uses of glass as a structural material. As architects begin to ask for more structural glass in their projects, structural engineers must be prepared to design the systems or to specify performance criteria to a specialty engineer. To aid in design, published guidelines and testing must be utilized and are therefore discussed. In a glass structural system, the glass is not the only aspect that needs an engineer's attention. Connections present a special challenge when designing with structural glass, but several different forms of connections have been successfully demonstrated in construction. To tie all the previous topics together, three examples of structural glass systems are presented. Europe has been using glass as a structural material for years, but the United States has been slow to follow the trend. Glass has been proven to work as a structural material that can create impressive visual impact. With the support of the glass manufacturing industry and the courage of design engineers, the United States could easily start a movement towards building with structural glass.
Keywords: Structural glass; Engineering, Civil (0543)